Facile Fluorescence “Turn on” Sensing of Lead Ions in Water via Carbon Nanodots Immobilized in Spherical Polyelectrolyte Brushes - Tian, Yuchuan; Kelarakis, Antonios; Li, Li; Zhao, Fang; Wang, Yunwei; Wang, Weihua; Yang, Qingsong; Ye, Zhishuang; Guo, Xuhong (Frontiers in Chemistry, 2018)
Heavy metal detection has become very important for the protection of water resource. In this work, a novel controllable probe is presented for the sensitive detection of Pb2+ in aqueous solutions. The probe was synthesized via the immobilization of surface functionalized carbon dots (named as CAEA-Hs) into the shell of the spherical polyelectrolyte brushes (SPB). The fluorescence of CAEA-H was firstly “turned off” via electrostatic interaction induced quenching. Based on the aggregation induced emission enhancement (AIEE), the fluorescence of the immobilized CAEA-H could be specifically turned on via the aggregation of the SPB particles. This fluorescence “turn on” sensor could selectively detect Pb2+ among 5 different metal ions with a relatively wide detecting range (0 mM-1.67 mM) and good linear relationship (R2 = 0.9958). Moreover, the aggregating behavior and nano-structure of CAEA-H loaded SPB have been systematically analyzed via small angle X-ray scattering, turbidity titration, and Zeta-potential measurement. Based on a series of control experiments, we finally gain an insight into the sensing mechanism of this novel sensing probe.